EEG Resting State Functional Connectivity in Adult Dyslexics Using Phase Lag Index and Graph Analysis - Fraga González, Gorka; Smit, Dirk J. A.; van der Molen, Melle J. W.; Tijms, Jurgen; Stam, Cornelis Jan; de Geus, Eco J. C.; van der Molen, Maurits W. (Frontiers in Human Neuroscience, 2018)
Developmental dyslexia may involve deficits in functional connectivity across widespread brain networks that enable fluent reading. We investigated the large-scale organization of EEG functional networks at rest in 28 dyslexics and 36 typically reading adults. For each frequency band, we assessed functional connectivity strength with the phase lag index (PLI). Network topology was examined using minimum spanning tree (MST) graphs derived from the functional connectivity matrices. We found significant group differences in the alpha band (8-13 Hz). The graph analysis indicated more interconnected nodes, in dyslexics compared to typical readers. The graph metrics were significantly correlated with age in dyslexics but not in typical readers, which may indicate more heterogeneity in maturation of brain networks in dyslexics. The present findings support the involvement of alpha oscillations in higher cognition and the sensitivity of graph metrics to characterize functional networks in adult dyslexia. Finally, the current results extend our previous findings on children.